Faktor yang Berhubungan dengan Kejadian Gizi Buruk pada Balita di Wilayah Kerja Puskesmas Tanggaba, Kabupaten Sumba Barat Daya - Meliati Tripenal Noni Lende; Petrus Romeo; Daniela L. A. Boeky (Universitas Nusa Cendana, 2022)
Health problems that have not been resolved in East Nusa Tenggara due to the large number and spread in all districts/cities, namely the problem of malnutrition. It is difficult to solve the problem of malnutrition because of the variables inherent in people's lives such as low public knowledge, low parenting, infectious disease factors and also low economic problems. This study aims to determine whether there is a relationship between maternal knowledge, parenting styles, history of infectious diseases and family economic relations with the incidence of malnutrition among children under five in the Work Area of ​​the Tanggaba Community Health Center, Southwest Sumba Regency. This research was designed as an analytic observational study, with a case control approach. The sample size was 76 people, divided into 38 case samples and 38 control samples. The data analysis used were univariate and bivariate. The results of this study indicate that there is a relationship between variables and the incidence of malnutrition in children under five, namely maternal knowledge (p-value=0.00), maternal parenting (p-value=0.00), history of infectious diseases (p-value=0.00) and economic problems (p-value=0.00). It is expected that parents, especially mothers of toddlers, always pay attention to the toddler's diet, toddler nutritional status and always clean up the surrounding environment in order to avoid the occurrence of malnutrition or malnutrition and avoid disease.